2010
DOI: 10.1097/jto.0b013e3181eba7f9
|View full text |Cite
|
Sign up to set email alerts
|

Modest Reductions in Dose Intensity and Drug-Induced Neutropenia have No Major Impact on Survival of Patients with Non-small Cell Lung Cancer Treated with Platinum-Doublet Chemotherapy

Abstract: This retrospective analysis demonstrates no significant relationship between survival and dose intensity (<90%), modest dose reductions (<20%), or chemotherapy-induced neutropenia in patients receiving standard doublet platinum containing chemotherapy in NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
1
17
1
Order By: Relevance
“…Six studies reported RDI and overall survival in metastatic lung cancer: five in non-small cell lung cancer (NSCLC) and one in small cell lung cancer [13][14][15][16][17][18]. Of these six studies, two analyzed overall survival by RDI (Table 2) [13,18].…”
Section: Lung Cancermentioning
confidence: 97%
“…Six studies reported RDI and overall survival in metastatic lung cancer: five in non-small cell lung cancer (NSCLC) and one in small cell lung cancer [13][14][15][16][17][18]. Of these six studies, two analyzed overall survival by RDI (Table 2) [13,18].…”
Section: Lung Cancermentioning
confidence: 97%
“…Several published articles have described a positive impact of chemotherapy-induced neutropenia on survival [3][4][5][6][7][8] . Conversely, other studies illustrated no effect, or an adverse impact on survival [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…A correlation has been noted between dose intensity and efficacy in some clinical trials (22,23). However, in ovarian cancer and non-small cell lung cancer, dose modifications of specific treatments had no impact on clinical outcomes (24,25). A post hoc analysis of a phase II trial of nab-P monotherapy in metastatic breast cancer also revealed no association of dose reduction with OS (26).…”
Section: Introductionmentioning
confidence: 99%